Substrate Pathways and Mechanisms of Inhibition in the Sulfur Oxygenase Reductase of Acidianus Ambivalens - Veith, Andreas; Urich, Tim; Seyfarth, Kerstin; Protze, Jonas; Frazão, Carlos; Kletzin, Arnulf (Frontiers in Microbiology, 2011)
Background: The sulfur oxygenase reductase (SOR) is the initial enzyme of the sulfur oxidation pathway in the thermoacidophilic Archaeon Acidianus ambivalens. The SOR catalyzes an oxygen-dependent sulfur disproportionation to H2S, sulfite and thiosulfate. The spherical, hollow, cytoplasmic enzyme is composed of 24 identical subunits with an active site pocket each comprising a mononuclear non-heme iron site and a cysteine persulfide. Substrate access and product exit occur via apolar chimney-like protrusions at the fourfold symmetry axes, via narrow polar pores at the threefold symmetry axes and via narrow apolar pores within in each subunit. In order to investigate the function of the pores we performed site-directed mutagenesis and inhibitor studies. Results: Truncation of the chimney-like protrusions resulted in an up to sevenfold increase in specific enzyme activity compared to the wild type. Replacement of the salt bridge-forming Arg99 residue by Ala at the threefold symmetry axes doubled the activity and introduced a bias toward reduced reaction products. Replacement of Met296 and Met297, which form the active site pore, lowered the specific activities by 25–55% with the exception of an M296V mutant. X-ray crystallography of SOR wild type crystals soaked with inhibitors showed that Hg2+ and iodoacetamide (IAA) bind to cysteines within the active site, whereas Zn2+ binds to a histidine in a side channel of the enzyme. The Zn2+ inhibition was partially alleviated by mutation of the His residue. Conclusions: The expansion of the pores in the outer shell led to an increased enzyme activity while the integrity of the active site pore seems to be important. Hg2+ and IAA block cysteines in the active site pocket, while Zn2+ interferes over a distance, possibly by restriction of protein flexibility or substrate access or product exit.